Reduced GABA concentration in patients with white matter hyperintensities - Wang, Xin; Wang, Caihong; Miao, Peifang; Wei, Ying; Lin, Liangjie; Li, Zhen; Zhang, Yong; Cheng, Jingliang; Ren, Cuiping (Frontiers in Neuroscience, 2023)
To investigate potential alterations of white matter hyperintensities (WMHs) on J-edited MR spectroscopy (MRS) measures of the primary inhibitory neurotransmitter γ-aminobutyric acid (GABA). Twenty-four WMHs patients and 20 healthy controls (HCs) were recruited to undergo magnetic resonance spectroscopy (MRS) scan at 3T from voxels in left centrum semiovale white matter, using the MEGA point resolved spectroscopy (MEGA-PRESS) technique with the MATLAB-based Gannet tool to estimate GABA + co-edited macromolecule (GABA+) levels and using Tarquin software to estimate levels of glutamate+glutamine (Glx), total N-acetylaspartate (tNAA), total choline (tCho), and total creatine (tCr). Independent t-tests or Mann-Whitney U tests were used to test group differences between WMHs and HCs.Additionally, WMHs patients were divided into mild and moderate-severe WMHs subgroup according to the Fazekas scale. Analysis of variance (ANOVA) and post hoc tests were used among WMHs subgroups and HCs. We found there was a significant reduction in GABA+ levels (p = 0.018) in WMHs patients compared with healthy controls. In subgroup analyses, there was also a significant reduction of GABA+ levels in moderate-severe WMHs subgroup (p = 0.037) and mild WMHs subgroup (p = 0.047) when compared to HCs. Besides, the moderate-severe WMHs subgroup had significantly higher levels of tCho compared with healthy controls (p = 0.019). In conclusion, reduced GABA+ levels in WMHs patients and elevated tCho levels in moderate-severe WMHs were observed when compared with HCs. These results demonstrate that abnormalities of the GABAergic system and choline metabolism may contribute to the pathogenesis of WMHs.